2010
DOI: 10.2165/11539140-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Gadoterate Meglumine (Gd-DOTA) as a Contrast Agent for Magnetic Resonance Imaging

Abstract: Background: Safety is a primary concern with contrast agents used for MRI. If precautions could be taken before the repeated administration of gadolinium-based contrast media, then the awareness and management of adverse reactions would be more efficient.Objectives: To assess the safety and efficacy of gadoterate meglumine (Gd-DOTA) [Magnescope® in Japan, Dotarem® in other countries], a gadolinium-based contrast agent, in patients undergoing imaging of the brain/spinal cord and/or trunk/limbs, and to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 20 publications
8
35
0
3
Order By: Relevance
“…Another analysis of 4,549 patients from 34 clinical trials reported a higher ADR incidence rate of 4.0 % [14], which can be attributed to the different methodology of data collection in randomized controlled clinical trials – including, for example, a longer follow-up duration (from 24 h to 7 days after gadobutrol administration) than in the current study, which followed routine clinical practice. Generally similar ADR rates have been reported for other GBCAs (Table 7) [13, 14, 1822]. …”
Section: Discussionsupporting
confidence: 84%
“…Another analysis of 4,549 patients from 34 clinical trials reported a higher ADR incidence rate of 4.0 % [14], which can be attributed to the different methodology of data collection in randomized controlled clinical trials – including, for example, a longer follow-up duration (from 24 h to 7 days after gadobutrol administration) than in the current study, which followed routine clinical practice. Generally similar ADR rates have been reported for other GBCAs (Table 7) [13, 14, 1822]. …”
Section: Discussionsupporting
confidence: 84%
“…The mean (standard error of the mean) serum creatinine values (μmol/l) at baseline and 48 h post-procedure were 330.9 (42.2) and 306.2 (44.7), respectively, in the Gd-DOTA group and 329.7 (53.9) and 344.6 (64.9), respectively, in the control group. This absence of impact on renal function was also recently documented in a post-marketing study conducted in 3,444 Japanese patients [7]. Kidney function tests, performed as part of routine medical care in patients with impaired renal function, did not reveal any significant difference in terms of serum creatinine values (μmol/l; mean ± standard deviation) before (194.5 ± 194.5) and after (203.3 ± 194.5) Gd-DOTA administration.…”
Section: Discussionsupporting
confidence: 61%
“…The absence of CIN after Gd-DOTA administration was initially demonstrated in a small, randomised study conducted in CKD patients [6]. The absence of impact of Gd-DOTA on renal function was further documented in a large Japanese post-marketing study [7], and its good overall safety was confirmed in a surveillance study of 84,621 patients, including 764 patients with renal failure [8]. In a retrospective study conducted by Ergün et al [9] in 91 patients with stage 3 and 4 CKD [mean eGFR by the modified MDRD formula (Modification of Diet in Renal Disease): 33 ml/min/1.73 m 2 ] assessed by magnetic resonance imaging (MRI) with an intravenous dose of 0.2 mmol/kg of Gd-DOTA, gadopentetate dimeglumine, or gadodiamide, 11 patients (12.1 %) developed CIN.…”
Section: Introductionmentioning
confidence: 99%
“…Doses of Gd-DOTA up to 0.325 mL/Kg and even uncommon greater than 0.2 mM/Kg were employed in patients [27].…”
Section: Discussionmentioning
confidence: 99%